Prospective ARNI vs. ACE inhibitor trial to DetermIne Superiority in reducing heart failure Events after Myocardial Infarction (PARADISE‐MI): design and baseline characteristics. (22nd April 2021) - Jering, Karola S.; Claggett, Brian; Pfeffer, Marc A.; Granger, Christopher; Køber, Lars; Lewis, Eldrin F.; Maggioni, Aldo P.; Mann, Douglas; McMurray, John J.V.; Rouleau, Jean‐Lucien; Solomon, Scott D.; Steg, Philippe G.; et al.
Abstract: Aims: Patients surviving an acute myocardial infarction (AMI) are at risk of developing symptomatic heart failure (HF) or premature death. We hypothesized that sacubitril/valsartan, effective in the treatment of chronic HF, prevents development of HF and reduces cardiovascular death following high‐risk AMI compared to a proven angiotensin‐converting enzyme (ACE) inhibitor. This paper describes the study design and baseline characteristics of patients enrolled in the Prospective ARNI vs. ACE inhibitor trial to DetermIne Superiority in reducing heart failure Events after Myocardial Infarction (PARADISE‐MI) trial. Methods and results: PARADISE‐MI, a multinational (41 countries), double‐blind, active‐controlled trial, randomized patients within 0.5–7 days of presentation with index AMI to sacubitril/valsartan or ramipril. Transient pulmonary congestion and/or left ventricular ejection fraction (LVEF) ≤40% and at least one additional factor augmenting risk of HF or death (age ≥70 years, estimated glomerular filtration rate <60 mL/min/1.73 m 2, diabetes, prior myocardial infarction, atrial fibrillation, LVEF <30%, Killip class ≥III, ST‐elevation myocardial infarction without reperfusion) were required for inclusion. PARADISE‐MI was event‐driven targeting 708 primary endpoints (cardiovascular death, HF hospitalization or outpatient development of HF). Randomization of 5669 patients occurred 4.3 ± 1.8 days from presentation with index AMI. The mean age was 64 ± 12 years, 24% were women. The majority (76%) qualified with ST‐segment elevation myocardial infarction; acute percutaneous coronary intervention was performed in 88% and thrombolysis in 6%. LVEF was 37 ± 9% and 58% were in Killip class ≥II. Conclusions: Baseline therapies in PARADISE‐MI reflect advances in contemporary evidence‐based care. With enrollment complete PARADISE‐MI is poised to determine whether sacubitril/valsartan is more effective than a proven ACE inhibitor in preventing development of HF and cardiovascular death following AMI. Abstract : PARADISE‐MI study design. AMI, acute myocardial infarction; CV, cardiovascular; eGFR, estimated glomerular filtration rate; HF, heart failure; LVEF, left ventricular ejection fraction; MI, myocardial infarction; STEMI, ST‐elevation myocardial infarction.